Capacitive deionization of arsenic-contaminated groundwater in a single-pass mode. (October 2017) - Fan, Chen-Shiuan; Liou, Sofia Ya Hsuan; Hou, Chia-Hung
Abstract: A single-pass-mode capacitive deionization (CDI) reactor was used to remove arsenic from groundwater in the presence of multiple ions. The CDI reactor involved an applied voltage of 1.2 V and six cell pairs of activated carbon electrodes, each of which was 20 × 30 cm 2 . The results indicate that this method achieved an effluent arsenic concentration of 0.03 mg L −1, which is lower than the arsenic concentration standard for drinking water and irrigation sources in Taiwan, during the charging stage. Additionally, the ability of the CDI to remove other coexisting ions was studied. The presence of other ions has a significant influence on the removal of arsenic from groundwater. From the analysis of the electrosorption selectivity, the preference for anion removal could be ordered as follows: NO3 −  > SO4 2−  > F −  > Cl − >As. The electrosorption selectivity for cations could be ordered as follows: Ca 2+  > Mg 2+  > Na +  ∼ K + . Moreover, monovalent cations can be replaced by divalent cations at the electrode surface in the later period of the electrosorption stage. Consequently, activated carbon-based capacitive deionization is demonstrated to be a high-potential technology for remediation of arsenic-contaminated groundwater. Highlights: Capacitive deionization was operated in a single-pass mode for groundwater remediation. An arsenic concentration of 0.03 mg L −1 in the effluent was achieved. The electrosorption selectivity towards arsenic-contaminated groundwater was studied. The replacement of monovalent cations with divalent cations was observed.